PERSEPSI MASYARAKAT TERHADAP JAMAAH TABLIGH DI GOBAH V SURAU NAGARI KOTO TANGAH TILATANG KAMANG KABUPATEN AGAM - Yoggi Dawatul Qarimah; Tomi Hendra (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The background of this research is that Jama'ah Tabligh as a da'wah group, has a method or method that is different from other Jama'ah Tabligh movement groups in general, they carry out da'wah by leaving the village where they live to another village. Staying at the mosque by visiting residents' homes reminding them of the importance of faith and good deeds in the afterlife. How to preach Islamic teachings with this method does not gain support from the community. This type of research uses descriptive qualitative research using a descriptive approach. Descriptive research means that the research is carried out only with the aim of describing a state or status phenomenon in a particular situation, including relationships, activities, attitudes, views, and the occurrence of the phenomenon. Data collection was carried out by making observations (observations), interviews, documentation, and looking for research results in the field. This type of research in this study was faced with various considerations, namely first to make it easier to describe research results so that they are easy to understand, second, research is expected to be able to build kinship between researchers and informants so that researchers can present data in the form of facts that occur in the field. From the results of research conducted at Gobah V Surau Tilatang Kamang where people's perceptions of jama'ah tabligh are divided into two, the first community who practice the teachings of Islam have succeeded in inviting people who come to the mosque to carry out their worship. worship, but after the presence of the tabligh congregation group you can see the people who come to pray at the mosque are getting better day by day. The form of teaching used by the tabligh congregation in Gobah V Surau which is the ideology of the movement understood by members of the tabligh congregation are twenty ushuk al-dakwah which must be obeyed by a preacher in carrying out khuruj.